2015 SPCTPD/ACC/AAP/AHA Training Guidelines for Pediatric Cardiology Fellowship Programs (Revision of the 2005 Training Guidelines for Pediatric Cardiology Fellowship Programs). Issue 6 (11th August 2015) - Ross, Robert D.; Brook, Michael; Koenig, Peter; Feinstein, Jeffrey A.; Lang, Peter; Spicer, Robert L.; Vincent, Julie A.
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.